To Asses the Knowledge of Women in Regards to Antenatal Care (Medical Forum Monthly, 2024)
Objective: To evaluate the awareness of women associated to antenatal care at Asian Institute of Medical Sciences Hyderabad.Study Design: Observational studyPlace and Duration of Study: This study was conducted at Gynae/Obs Outpatient Department of Asian Institute of Medical Sciences Hyderabad and LUMHS Hyderabad from 1st January 2014 to June 30th, 2014.Materials and Methods: Total 150 women were selected in the study. All the awareness regarding antenatal care of the women was documented on Performa.Results: Total 150 women were selected in the study, mostly cases 53.3% were more than 31 years of the age. Majority of the women 64.4% were uneducated. 69% chose doctors as primary provider for antenatal care, 11% nurses, 19% trained birth attendants. 52% women wished to receive care at home while 47% said at hospital. 70% responded yes to understanding what antenatal care was while 30% had no awareness. 89% of women responded yes it is necessary to have antenatal care while 11% responded that no it is not necessary. Conclusion: Awareness regarding antenatal is very rare in the women. Women seek antenatal care only when they are symptomatic and not as a preventive or screening measure. The time of pregnancy is a necessary time period during which the promotion of healthy behaviours is imperative. Participation of the family members and the community can perform a very important role for healthy women during pregnancy.